Aspects in Formulating Mathematical Model of Wind Turbine - Waleed Khalil Ahmed (Bulletin of Electrical Engineering and Informatics, 2013)
The present paper explores the mathematical molding of the wind turbine and its influence on the subsequent stages. Specifically, the paper investigate the modeling of gear train of the wind turbine and distinguishes the difference in the approaches usually used to establish the mathematical model which is later has a significant impact on the design, characteristic and performance of the modeled system. Mainly two commonly used approached for the gear train systems are analyzed and discussed. The main well know mechanisms are investigated in term of the most proposed assumptions to deal with the damping, shaft stiffness and inertia effect of the gear. This paper elucidates these concerns.